Discovery of the Sun's million-degree hot corona - Peter H.; Dwivedi B.N. (My University, 2025)
As time goes by, discoveries become common knowledge, and often the person who first changed a paradigm gets forgotten. One such case is the discovery that the Sun's corona is a million degrees hot—much hotter than its surface. While we still work on solving how the Sun heats the corona, the name of the discoverer seems to be forgotten. Instead, other people get the credit who contributed important pieces to the puzzle, but the person who solved this puzzle was someone else. In this historical note we show that this credit should go to Hannes Alfvén (cf. Figure 1). © Copyright © 2014 Peter and Dwivedi.